Comparison of Different Test Systems for the Detection of Antiphospholipid Antibodies in a Chinese Cohort - Hu, Chaojun; Li, Siting; Xie, Zhijuan; You, Hanxiao; Jiang, Hui; Shi, Yu; Qi, Wanting; Zhao, Jiuliang; Wang, Qian; Tian, Xinping; Li, Mengtao; Zhao, Yan; et al. (Frontiers in Immunology, 2021)
Background: Diagnosis of antiphospholipid syndrome (APS) is based on the positivity of laboratory criteria antiphospholipid antibodies (aPLs). Test results for aPLs could be contradictory among different detection methods as well as commercial manufacturers. This study aimed to assess and compare the diagnostic and analytic performances of four commercial assays prevalently used in China. Methods: A total of 313 patients including 100 patients diagnosed with primary APS, 52 with APS secondary to SLE, 71 with SLE, and 90 health controls were recruited. Serum IgG, IgM, and IgA for aCL and aβ2GPI antibodies were detected with two ELISA and two CLIA systems, and test system with best diagnostic value was explored of its correlation with key clinical features. Results: CLIA by YHLO Biotech Co. was considered as the system with best predictive power, where 58.55% and 57.89% of APS patients was positive for aCL or aβ2GPI for at least one antibodies (IgG or IgM or IgA). Overall, CLIA showed better performance characteristics than traditional ELISA test systems. Conclusion: CLIA was considered as a better platform for aPLs detection in APS diagnosis. Combination of other detection platforms could assist in differential diagnosis, increase the ability of excluding SNAPS, as well as identifying high-risk patients.